Microwave Photonic Frequency Up-Convertor With Frequency Doubling and Compensation of Chromatic-Dispersion-Induced Power Fading - Chunjing Yin; Jianqiang Li; Bingyu Li; Qiang Lv; Jian Dai; Feifei Yin; Yitang Dai; Kun Xu (IEEE Photonics Journal)
A novel photonic frequency-doubling up-convertor with compensation of chromatic-dispersion-induced power fading is proposed and experimentally demonstrated based on the cascaded structure of a Mach–Zehnder modulator (MZM) and a dual-parallel Mach–Zehnder modulator (DPMZM). The MZM is driven by a local oscillator signal biased at the null point for carrier-suppressed double-sideband modulation. The DPMZM is single-port driven by the intermediate-frequency signal and the other port is matched with a 50-Ω resistance. By adjusting the dc biases of the DPMZM, the power fading induced by chromatic dispersion can be compensated at any frequency. Experimentally, comparing with the conventional up-conversion radio-over-fiber link with cascaded MZMs, the power fading in 60 and 80 km fiber links can be successfully compensated and a 26.7 dB improvement in spurious-free dynamic range at 21.7 GHz for a link of 60 km can be achieved by using the proposed scheme.